2019
DOI: 10.1155/2019/1427294
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Motor Profile in Preschool Children with Primary Stereotypic Movement Disorder

Abstract: Aim. Different neuropsychological dysfunctions have been described in children with primary Stereotypic Movement Disorder (SMD), mainly attention or motor coordination problems. Up to now with no study has evaluated psychomotor functions in preschoolers primary SMD. The aim of this observational study was to gather information on the motor profiles of SMD patients in this age range in comparison with typically developing children. Patients and Methods. Twenty-six children (four girls) aged 36 to 76 months (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
0
15
0
3
Order By: Relevance
“…Another study reported a negative impact on VMI skills in children with primary stereotypic movement disorder [ 70 ]. Overall, the literature was at a consensus that diagnosis impacts VMI skills [ 66 70 ]. Table 6 provides a summary of the findings.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Another study reported a negative impact on VMI skills in children with primary stereotypic movement disorder [ 70 ]. Overall, the literature was at a consensus that diagnosis impacts VMI skills [ 66 70 ]. Table 6 provides a summary of the findings.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Three studies examined VMI deficits in children with coordination disorders [ 66 , 68 , 70 ]. Participation in activities was positively correlated with motor ability as captured by the VMI score in children with DCD [ 68 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations